CINE–PICC: SATISFACTION AND KNOWLEDGE FOLLOWING A VIDEO AND HANDS-ON TRAINING IN PERIPHERALLY INSERTED CENTRAL CATHETER - Eneida Rejane Rabelo da Silva; Ivana Duarte Brum; Sandra Leduina Alves; Marcos Rodrigo Garcia; Cristiane Vizcaychipi; Helena Becker Issi; Patrícia Bairros; Giovana Ely Flores; Fernanda Brazeiro Lemos; Deise Cristianetti (Clinical and Biomedical Research, 2022)
Objective: This study evaluated the knowledge and satisfaction of a nursing staff regarding the care of PICC before and after a combined training strategy consisting of video watching followed by hands-on practice; Methods: A cross-sectional and prospective study with data collection held at a public University Hospital from March to May 2018 and March 2019. The participants answered a pre-test about PICC, watched a video on PICC care and maintenance, watched a hands-on sessions and answered a pos-test. Results: A total of 520 professionals participated, in which 87.4% were from the nursing staff. A pre-test was answered by 211 and 203 answered the post-test questions. The satisfaction research covered a total of 97% satisfied respondents. Conclusions: Results indicate that the change from the traditional training model to an active educational approach reached a larger number of participants, showing up an innovative pedagogical tool in the training of critical and reflexive professionals.